Effect of PNBP Policy on The financial Performance of Cellular Mobile Network Operators - Ronny Ronny; Sartika Djamaluddin (Universitas Mercu Buana, 2023)
Digital transformation is one of the programs initiated by the Government, which in practice requires the support of healthy mobile network operators through financial performance indicators, to fulfill the development of telecommunications infrastructure in all regions. Mobile network operators require significant capital to provide telecommunications infrastructure, including payment of Non-Tax State Revenue (PNBP) to the government every year, which continues to increase due to frequency allocation and telecommunications activities. The aim of this research is to measure the estimated influence of PNBP policy on the financial performance of mobile network operators in Indonesia, while considering several other control variables such as investment costs (CAPEX), number of subscribers, liabilities, number of base transceiver stations (BTS), and number of mobile network operators. This research uses panel data regression with a fixed effect model approach, covering four mobile network operators from 2010 to 2022. The results show that PNBP, sourced from the obligation to pay Spectrum Frequency Usage Fee, has a significant negative impact on financial performance. These findings are also consistent with the research conducted by Katz and Jung (2023)